PENERAPAN SANKSI ADMINISTRATIF TERHADAP RUMAH SAKIT PELAKU FRAUD KLAIM JKN DALAM PERSPEKTIF HUKUM KESEHATAN - Mutia Annisa (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Fraudulent claims in Indonesia’s National Health Insurance (JKN) pose a serious threat to financial sustainability and quality of healthcare services. Hospitals, as referral healthcare providers, are highly vulnerable to fraudulent practices such as upcoding, phantom billing, and diagnosis manipulation. This study analyzes the regulation and effectiveness of administrative sanctions imposed on hospitals committing JKN claim fraud from a health law perspective. Using a normative legal research method with statutory, conceptual, and case approaches, this study finds that although administrative sanctions are normatively regulated, their implementation remains ineffective in creating deterrence and legal certainty. Sanctions tend to be formalistic and weakly enforced due to limited supervision and inter-institutional coordination. Strengthening regulations, supervision systems, and sanction standards is therefore essential to ensure legal protection and sustainability of JKN